Down-regulation of the antigen processing machinery is linked to a loss of inflammatory response in colorectal cancer - Kasajima, Atsuko; Sers, Christine; Sasano, Hironobu; Jöhrens, Korinna; Stenzinger, Albrecht; Noske, Aurelia; Buckendahl, Ann-Christin; Darb-Esfahani, Silvia; Müller, Berit Maria; Budczies, Jan; Lehman, Annika; Dietel, Manfred; et al. (Human pathology, 2010)
Antitumor inflammatory response is known to inhibit tumor growth in colorectal carcinoma. The density and functionality of tumor-infiltrating lymphocytes (TIL) is regulated by the antigen processing machinery through regulator proteins such as transporters associated with antigen processing (TAP) and major histocompatibility complex (MHC) class I antigen. We aimed to investigate the in vivo association of those factors and their impact on prognosis in colorectal cancer.